Arthroscopic anatomy and pathoanatomy of anterior cruciate ligament ruptures: clinical study with 94 patients: Artroskopska anatomija in patoanatomija raztrganine sprednje križne vezi: klinična raziskava z vključenimi 94 bolniki - Hussein, Mohsen; Čretnik, Andrej; Dinevski, Dejan; Rupreht, Mitja; Vogrin, Matjaž (Acta Medico-Biotechnica, 2021)
Purpose: To arthroscopically evaluate the size variability of the Anterior cruciate ligament (ACL) insertion sites and to determine whether there are variations in rupture patterns of the two ACL bundles.Material and Methods: Ninetyfour patients undergoing ACL reconstruction between June 2008 and June 2009 were included inour study. The average age of the patients was 26.7 ± 8.3 years (range, 16–48 years). Only patients with an ACL rupture less than 120 days old were included as unpublished data revealed difficulty in distinguishing between AM and PL bundles in older ACL ruptures.Results: The femoral ACL insertion site length ranged from 11 to 20 mm (15.9 ± 2.2). On the tibial side, the length of the tibial ACL insertion site ranged from 9 to 20 mm (16.0 ± 2.1). On the femoral side, the width of the ACL insertion site ranged from 6 to 11 mm (8.3 ± 1.2). On the tibial side, the width of the entire ACL insertion site ranged from 6 to 12 mm (8.7 ± 1.1). The most frequent injury pattern was found to be the proximal rupture of both bundles; seen in 74 patients (78.7%).Conclusion: Both hypotheses were confirmed, and this may be clinically relevant in anatomic ACL reconstruction.